Dirty thirty [compact disc, unabridged] - Evanovich, Janet (Evanovich, Janet. Stephanie Plum novel., 2023)
Stephanie Plum, Trenton's hardest working, most underappreciated bounty hunter, is offered a freelance assignment that seems simple enough. Local jeweler Martin Rabner wants her to locate his former security guard, Andy Manley (a.k.a. Nutsy), who he is convinced stole a fortune in diamonds out of his safe. Stephanie is also looking for another troubled man, Duncan Dugan, a fugitive from justice arrested for robbing the same jewelry store on the same day. With her boyfriend Morelli away in Miami on police business, Stephanie is taking care of Bob, Morelli's giant orange dog who will devour anything, from Stephanie's stray donuts to the upholstery in her car. Morelli's absence also means the inscrutable, irresistible security expert Ranger is front and center in Stephanie's life when things inevitably go sideways. And he seems determined to stay there. To complicate matters, her best friend Lula is convinced she is being stalked by a mythological demon hell-bent on relieving her of her wardrobe. An overnight stakeout with Stephanie's mother and Grandma Mazur reveals three generations of women with nerves of steel and driving skills worthy of NASCAR champions. As the body count rises and witnesses start to disappear, it won't be easy for Stephanie to keep herself clean when everyone else is playing dirty. It's a good thing Stephanie isn't afraid of getting a little dirty, too.